Oxalate nephropathy following Roux-en-Y gastric bypass surgery - Mini-Review - Verdelho,Miguel (2016)
Oxalate Nephropathy is characterised by the presence of tubular crystalline deposits of calcium oxalate, which can lead to both acute and chronic tubular injury and progressive renal failure. Enteric hyperoxaluria is the most common cause of moderate hyperoxaluria; it occurs in conditions associated with fat or bile acid malabsorption, which include jejunoileal bypass and other bariatric procedures such as Roux-en-Y gastric bypass surgery. We present the clinical case of a 69-year-old man who was hospitalised for non-oliguric renal dysfunction, with a serum creatinine of 10 mg/dl and normocytic normochromic anaemia. There was no prior history of renal disease. Twenty months before admission the patient was diagnosed with a gastro-oesophageal junction adenocarcinoma and was treated with pre-operative chemotherapy, followed by total gastrectomy, with a Roux-en-Y gastric bypass reconstruction. On discharge from gastric surgery, renal function was normal. On the first day of hospital stay haemodialysis was initiated. Over the following days, the rapid unexplained renal impairment was investigated, and this workup [2] included a kidney biopsy. Histological examination of the biopsy specimen revealed a predominantly interstitial nephropathy with tubular atrophy and interstitial fibrosis, with bright intra-tubular calcium oxalate crystals in over 50% of the tubules and so the histological diagnosis was of oxalate nephropathy. Subsequently, no recovery of renal function was observed, so the patient is currently undergoing regular haemodialysis. Oxalate nephropathy is a rare but severe complication of Roux-en-Y gastric bypass surgery that can lead to a rapid progression to kidney failure. Although the treatment of obesity is the main indication for this surgery, this is also the preferred approach for gastrointestinal reconstruction after total gastrectomy for treatment of gastric carcinoma. Considering the rapid progression of oxalate nephropathy to kidney failure, patients who undergo Roux-en-Y gastric bypass surgery should have regular follow-up of renal function.